2015
DOI: 10.1016/j.jesp.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses and math performance: The role of stereotype threat and anxiety reappraisals

Abstract: This research independently manipulated two potential attenuators of stereotype threat -reappraisal of anxiety and test framing -to explore their independent and combined effects. Female participants took a difficult math exam that was described as gender-biased or gender-fair and were told that anxious arousal could positively impact performance or were given no information regarding arousal. Levels of the cytokine Interleukin-6 (IL-6), an immune marker of inflammation, were measured in oral mucosal transudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 27 publications
(33 reference statements)
1
47
1
Order By: Relevance
“…A power analysis based on an average effect size ( d =.66) from similar social-situational intervention research in laboratory settings using standardized social stress induction paradigms led to a targeted sample of 30 participants per condition (Beltzer, Nock, Peters, & Jamieson, 2014; Jamieson et al, 2010; Jamieson, Nock, & Mendes, 2012; Jamieson, Nock, et al, 2013; John-Henderson, Rheinschmidt, & Mendoza-Denton, 2015). A total of N =60 high school students were recruited from the Rochester, NY area using posted flyers and study information distributed by peers/teachers.…”
Section: Methodsmentioning
confidence: 99%
“…A power analysis based on an average effect size ( d =.66) from similar social-situational intervention research in laboratory settings using standardized social stress induction paradigms led to a targeted sample of 30 participants per condition (Beltzer, Nock, Peters, & Jamieson, 2014; Jamieson et al, 2010; Jamieson, Nock, & Mendes, 2012; Jamieson, Nock, et al, 2013; John-Henderson, Rheinschmidt, & Mendoza-Denton, 2015). A total of N =60 high school students were recruited from the Rochester, NY area using posted flyers and study information distributed by peers/teachers.…”
Section: Methodsmentioning
confidence: 99%
“…Those who valued negative emotions (e.g., anger, nervousness) showed weaker links between the negative emotions they experienced day-to-day and poor psychosocial functioning and physical health (Luong et al, 2015). Other studies have shown that inducing positive beliefs about the functionality of specific emotional states (e.g., anxiety) or features (e.g., physiological arousal) promotes recovery from stressful situations (Low et al, 2008;Jamieson et al, 2010Jamieson et al, , 2012John-Henderson et al, 2015), and wellbeing (Chow and Berenbaum, 2016). The fact that negative emotions can be viewed as useful shows that people's beliefs about the functionality of emotion do not simply reflect how they want to feel (Chow et al, 2015), or how pleasurable they perceive certain feelings to be (Netzer et al, 2018).…”
Section: Lay Beliefs About the Functionality Of Specific Emotional Stmentioning
confidence: 99%
“…Second, past research grounded in the BPS model of challenge and threat has most frequently studied situation-specific or acute stress processes in targeted motivated-performance situations (e.g., classroom mathematics exams; Jamieson, Peters, Greenwood, & Altose, 2016;John-Henderson, Rheinschmidt, & Mendoza-Denton, 2015). However, less research has examined whether situation-general belief systems, such as implicit theories of intelligence can differentially predict appraisals and physiological responses (for exceptions, see Chen, Langer, Raphaelson, & Matthews, 2004;Crum et al, 2013).…”
Section: Contributions Of the Present Researchmentioning
confidence: 99%